2010
DOI: 10.1097/naq.0b013e3181d91851
|View full text |Cite
|
Sign up to set email alerts
|

Dance-Based Therapy in a Program of All-inclusive Care for the Elderly

Abstract: Dance therapy results in positive functional trends, suggesting that further study using dance-based therapy will be useful to decrease fall risks in older persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 18 publications
2
40
0
7
Order By: Relevance
“…Alpert et al (2009) reported an increasing trend on the Equitest Sensory Organization Test in 13 women aged 52–88 undergoing jazz dance for 15 weeks. Krampe et al (2010) observed in 11 older adults an increasing trend in time up-and-go and functional reach after a 6-week dance intervention based on the Lebed method.…”
Section: Introductionmentioning
confidence: 99%
“…Alpert et al (2009) reported an increasing trend on the Equitest Sensory Organization Test in 13 women aged 52–88 undergoing jazz dance for 15 weeks. Krampe et al (2010) observed in 11 older adults an increasing trend in time up-and-go and functional reach after a 6-week dance intervention based on the Lebed method.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of efficiency of neuro muscular connections and slowing of information processing leads to slower reaction time and locomotor adjustments, this in turn results in maintaining body's balance during static and dynamic movements thus to slow this deterioration of balance one should gradually and continuously stimulate balance through motor activity. Many studies have reported that dance based exercises/ therapy improves balance and gait in elderly individuals [22,17,16], but these are behavioral studies show functional modifications in balance system. Hence from the present study it can be postulated from the objective method that dance based therapy/exercises can be used to reduce fall risks in elderly in order to have significant psycho social benefits and improve their perception of their life.…”
Section: Discussionmentioning
confidence: 99%
“…There are various reports which suggest that dance based training improves balance function in young as well as adult subjects. [16,17].…”
Section: Page 7748mentioning
confidence: 99%
“…Volp (2010) Também foi encontrada, com o indicador "todas as palavras" para a consulta do termo "dança-educação", uma produção no currículo de um líder na área de Ecologia, mas nenhuma ocorrência com a opção "frase exata". O interesse por este campo de estudo pode estar no objetivo de evidenciar a transdisciplinaridade e contribuir com as relações entre educação e desenvolvimento humano e social, conforme descrito nas repercussões dos trabalhos do grupo que tem a Educação Biocêntrica como um foco de interesse (BRASIL, 2010 De acordo com Krampe et al (2010), atividades físicas baseadas na dança podem contribuir para a diminuição dos fatores de risco à saúde e resultam em tendências positivas também em idosos. Com estes apontamentos, torna-se possível inferir que a percepção de desenvolvimento de habilidades pessoais por intermédio das vivências em dança pode constituir-se como um meio de intervenção na saúde e vir a influenciar, de forma positiva, a qualidade de vida, especialmente no que concerne aos aspectos referentes às vivências e experiências mais sensíveis, saudáveis e prazerosas.…”
Section: Eixo Temático Principal -Publicações De Artigos Completos Dounclassified